Diclofenac Sodium Inhibits Hepatic Tryptophan 2,3-Dioxygenase but Augments Brain Indoleamine 2,3-Dioxygenase Activities in Rats - Shazia Dawood; Elvis O. Wambiya; Samina Bano (Journal of Basic & Applied Sciences, 2016)
Tryptophan 2,3-dioxygenase (TDO) exist only in liver while indoleamine 2, 3-dioxygenase (IDO) exists ubiquitously in the body, these are the most rate-limiting enzymes of kynurenine pathway (KP). In response to elevated levels of cortisol and pro-inflammatory cytokines, both enzymes show increase activity in patients with depression or Alzheimer disease (AD). Non-steroidal anti-inflammatory drugs may protect against both depression and AD, but observational studies have offered contradictory results. Present study evaluates the effects of anti-inflammatory diclofenac sodium (DS) on rat hepatic TDO and brain IDO activities. Adult Albino Wistar rats were divided into control and test groups, each test group received DS (2mg/kg) i.p. injection daily and were killed either after 3.5 hours (acute treatment) or after 3, 5 and 7 days (chronic treatment) while control groups received an equal volume of vehicle. Results show that TDO enzyme activity was inhibited and liver tryptophan concentrations were increased after 3 to 7 days treatment of DS; however no effect was seen on these parameters after 3.5hrs. Brain IDO activity was increased after both acute and chronic DS treatment. It is concluded that DS inhibits hepatic TDO enzyme activity following chronic treatment, while augments brain IDO activity following both acute and chronic DS treatment, this may result in rise in cerebral kynurenic acid and/or quinolinic acid concentrations. Therefore there is a need that effects of DS on kynurenine pathway should be further investigated to rule out the protective effect of DS in inflammation-induced depression and Alzheimer disease.